Receptie, tekst en muziek van Camphuysens Stichtelycke rymen - Schenkeveld-van, Riet (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2014)
Camphuysens’ Stichtelycke rymen (1624) was the most popular Dutch songbook in the seventeenth and eighteenth century. The article discusses the amazingly positive reception of this book with texts by a persecuted Arminian minister pleading for a life of rigorous virtuousness. The article argues that the positive reception can be explained, amongst other things, by the attractive musical style of the melodies, partly taken from popular secular Dutch songs, partly derived from modern composers like Dowland or Gastoldo, and partly totally new, probably composed by the author himself.